Experience stories on peasantry in Latin America: training, teaching and research - Varón Rojas, Diego Hernán (Facultad de Filosofía y Humanidades. Secretaria de Extensión, 2022)
This document socializes three significant experiences in processes of social organization of the peasantry in Latin America. The experiences were developed throughout my training as an anthropologist, then in the role of teacher, researcher and director of a graduate program. While participating in a qualification process, a day of observation was carried out in several municipalities of the State of Oaxaca - Mexico, as a member of a working group that integrates the Latin American Council of Social Sciences (CLACSO). It also included the social movement established by peasants in the department of Cusco - Peru, which was the object of analysis during a field trip. But many years before, as an undergraduate student, I participated in an academic stay with peasants in the south of the Colombian Andes, in the department of Cauca. These reflections are supported by the developments generated by the human sciences, particularly on the changes experienced by this population: the current demands for the prices of inputs, the need to increase the dignity and peasant identity, and the consideration of this work as an important issue in the world of work.